Error minimization in lateral inhibition circuits. - Barad, O.; Rosin, D.; Hornstein, E.; Barkai, N. (Science signaling, 2010)
The pattern of the sensory bristles in the fruit fly Drosophila is remarkably reproducible. Each bristle arises from a sensory organ precursor (SOP) cell that is selected, through a lateral inhibition process, from a cluster of proneural cells. Although this process is well characterized, the mechanism ensuring its robustness remains obscure. Using probabilistic modeling, we defined the sources of error in SOP selection and examined how they depend on the underlying molecular circuit. We found that rapid inhibition of the neural differentiation of nonselected cells, coupled with high cell-to-cell variability in the timing of selection, is crucial for accurate SOP selection. Cell-autonomous interactions (cis interactions) between the Notch receptor and its ligands Delta or Serrate facilitate accurate SOP selection by shortening the effective delay between the time when the inhibitory signal is initiated in one cell and the time when it acts on neighboring cells, suggesting that selection relies on competition between cis and trans interactions of Notch with its ligands. The cis interaction model predicts that the increase in ectopic SOP selections observed with reduced Notch abundance can be compensated for by reducing the abundance of the Notch ligands Delta and Serrate. We validated this prediction experimentally by quantifying the frequency of ectopic bristles in flies carrying heterozygous null mutations of Notch, Delta, or Serrate or combinations of these alleles. We propose that susceptibility to errors distinguishes seemingly equivalent designs of developmental circuits regulating pattern formation.